Nano-oxygenated hydrogels for locally and permeably hypoxia relieving to heal chronic wounds. (March 2022) - Yang, Zhengyang; Chen, Huanhuan; Yang, Peizheng; Shen, Xiaofei; Hu, Yiqiao; Cheng, Yuhao; Yao, Hongwei; Zhang, Zhongtao
Abstract: Exposed chronic wounds are usually covered by hypoxic tissues accompanied with necrosis, persistent inflammation and anaerobic infections. Since atmospheric oxygen air can only penetrate about 0.3 mm tissues, meanwhile oxygen from the circulation is difficult to reach chronic wounds through the destroyed blood vessels, a solution to deliver oxygen locally and permeably is urgently needed. Herein we report a technique to reform traditional gel-based wound dressings by adding lyophilized oxygen encapsulated nanoparticles, which can deliver dissolved oxygen locally into wound surface. This delivery technique can potentially evaluate the therapeutic effects on hypoxic epithelial, endothelial and fibroblasts in vitro . Further experiments confirm the effects on both open wounds bearing and flap transplanted diabetic mice models. Considering its biocompatibility, effectiveness and practicality, we believe our hydrogel has significant transformation value to care and accelerate the healing of various clinical wounds, especially chronic wound.